O matriciamento em saúde mental sob vários olhares - Iglesias, Alexandra (2015)
The mental health matrix support has a proposal of mental health integration with the Primary health care, and constitutes itself as an important knowledge and practices joint strategy for the realization of the purposes of the Health Care Reform and the Psychiatric Reform. It is a practice in the construction process on the network and that contradicts the capitalist logic, based on individualism, competitiveness and social segregation. Thus, it is necessary to put such practices under constant review in order not to reproduce the logic that you want overcome and, on the contrary, claims the priority pledge of Matrix Support to share knowledge and practices for comprehensive action. The objective of this thesis was to analyze the practices of Matrix Support in mental health conducted by CAPS (Psychosocial Care Centers) with the Primary Care in a municipality in southeastern Brazil. Therefore, we proceed with semi-structured interviews with professionals and managers involved in the support, with conversations in everyday life, participation in meetings and field observation, in addition to the documentary survey about the deployment history of the Matrix Support in mental health in this municipality. We used a qualitative approach and content analysis technique for the construction of meanings and understandings concerning the subject matter. This thesis is organized in eight studies of scientific articles format. From the theoretical framework of Health Promotion and deinstitutionalization we look back on the data to identify the issues, the relations and contradictions relevant to the understanding and the daily lives of Matrix Support practices. Despite the visible expansion of mental health care also for other network services, especially for primary care, there is still a lot to explore in matrix practice what we consider expensive in Health Care Reform and psychiatric reform: the de-medicalization of life and de-stigmatization of psychological distress. We currently have times when the matrix support with their knowledge and experiences intersection proposal can enable a broadening of health practices and others in which remains a practice that only bears the name of matrix, but is based on vertically integrated relationships. Be in one time or another, which is not being held in this city is the regular and longitudinal meeting between all the actors involved in this process.